Pengembangan Sistem Monitoring Kehadiran Siswa Dengan Bantuan Sms Gateway dan Extreme Programming - Euis Amanah; Selamet Samsugi; Siska Ayu Widiana; Eliasta Ketaren (Universitas Teknokrat Indonesia, 2023)
Student attendance at SMKN 1 Kebun Tebu is still done manually. The student affairs department often struggles when asked for information about student attendance. Many parents/guardians complained because they did not know the attendance information or delay of their children from the school. Communication devices in the form of cellular phones or mobile phones are not a luxury anymore but can be said to be a secondary need for everyone because the function is much more practical and efficient. These technological advances can be used as a reporting system about student information, especially attendance. Currently, there are still many schools that cannot maximize the technology at least to monitor children from anywhere without having to go to school just to ask about their children's attendance. Therefore, a web-based student attendance information system and SMS Gateway are needed to facilitate the process of monitoring students by parents. Using software development, the author tried to build a web-based student attendance information system with SMS Gateway at SMKN 1 Kebun Tebu using Java and PHP programming languages with MySql as the database. So that the input process and data processing are faster. With this application, it is expected to help the school and students in the student attendance process.